Evaluating Vitamin C in Septic Shock: A Randomized Controlled Trial of Vitamin C Monotherapy*. Issue 5 (5th January 2022) - Wacker, David A.; Burton, Susan L.; Berger, John P.; Hegg, A. J.; Heisdorffer, Jamie; Wang, Qi; Medcraft, Emily J.; Reilkoff, Ronald A.
Abstract : OBJECTIVES: To determine whether IV vitamin C therapy reduces 28-day mortality in patients with septic shock. DESIGN: Multicenter, double-blinded, randomized controlled trial. SETTING: One academic medical ICU and four community ICUs. PATIENTS: Of 167 adult patients within 24 hours of vasopressor initiation for septic shock, 126 consented to participation, and 124 received study drug and were included in analysis. INTERVENTIONS: IV vitamin C (10 mg/mL in normal saline) administered as a 1, 000-mg bolus over 30 minutes followed by continuous infusion of 250 mg/hr for 96 hours or placebo of equal volumes of normal saline. MEASUREMENTS AND MAIN RESULTS: Of 124 subjects receiving study drug and included in analysis, 60 received vitamin C and 64 placebo. The primary outcome of all-cause 28-day mortality (vitamin C, 26.7%; placebo, 40.6%; p = 0.10) was lower in the vitamin C arm but did not reach statistical significance. Initiation of renal replacement therapy was higher in the vitamin C arm (vitamin C, 16.7%; placebo, 3.3%; p = 0.015), as was volume of fluid administration within 6 hours of study drug initiation (vitamin C, 1.07 L; placebo, 0.76 L; p = 0.03). There were no statistically significant differences in other secondary outcomes. In post hoc subgroup analysis, there was a decrease in 28-day mortality in the vitamin C arm among patients requiring positive-pressure ventilation at the time of enrollment (vitamin C, 36.3%; placebo, 60.0%; p = 0.05). This trial is registered at clinicaltrials.gov under identifier NCT03338569. CONCLUSIONS: Vitamin C monotherapy failed to significantly reduce mortality in septic shock patients as hypothesized. Our findings do not support its routine clinical use for this purpose.